Extracellular interleukin‐17F has a protective effect in oral tongue squamous cell carcinoma. Issue 10 (14th May 2018) - Almahmoudi, Rabeia; Salem, Abdelhakim; Sieviläinen, Meri; Sundquist, Elias; Almangush, Alhadi; Toppila‐Salmi, Sanna; Paavonen, Timo; Salo, Tuula; Al‐Samadi, Ahmed
Abstract: Background: Oral tongue squamous cell carcinoma (SCC) is characterized by early metastasis and poor prognosis. Interleukin‐17F (IL‐17F) plays a protective role in many tumors. However, IL‐17F expression in oral tongue SCC tissue has not been investigated. Methods: Immunostaining of 83 oral tongue SCC specimens and blinded‐scoring were used to map IL‐17F expression, location, and distribution. Survival curves were constructed according to Kaplan‐Meier method. The Cox proportional hazard model was applied for univariate and multivariate survival analyses. Results: Mast cells are the major source of IL‐17F in oral tongue SCC. In multivariate analysis, only the extracellular mast cell‐derived IL‐17F at the tumor invasion front was associated with better disease‐specific survival in patients with all‐stages and early‐stages of oral tongue SCC. Conclusion: Extracellular mast cell‐derived IL‐17F is antitumorigenic in oral tongue SCC. It separates patients with early‐stage disease who are at high risk from patients who are at low risk. Furthermore, when analyzing tentative prognostic molecules, we conclude that in addition to the staining intensity, attention must be paid to the cellular source, distribution, and location of the molecule.